Virulence-attenuated Salmonella engineered to secrete immunomodulators reduce tumour growth and increase survival in an autochthonous mouse model of breast cancer. (21st April 2021) - Augustin, Lance B.; Milbauer, Liming; Hastings, Sara E.; Leonard, Arnold S.; Saltzman, Daniel A.; Schottel, Janet L.
Abstract: The ultimate goal of bacterial based cancer therapy is to achieve non-toxic penetration and colonisation of the tumour microenvironment. To overcome this efficacy-limiting toxicity of anticancer immunotherapy, we have tested a therapy comprised of systemic delivery of a vascular disrupting agent to induce intratumoral necrotic space, cannabidiol to temporarily inhibit angiogenesis and acute inflammation, and a strain of Salmonella Typhimurium that was engineered for non-toxic colonisation and expression of immunomodulators within the tumour microenvironment. This combination treatment strategy was administered to transgenic mice burdened with autochthonous mammary gland tumours and demonstrated a statistically significant 64% slower tumour growth and a 25% increase in mean survival time compared to control animals without treatment. These experiments were accomplished with minimal toxicity as measured by less than 7% weight loss and a return to normal weight gain within three days following intravenous administration of the bacteria. Thus, non-toxic, robust colonisation of the microenvironment was achieved to produce a significant antitumor effect.